ANALYSIS OF LENONG BETAWI ART AS A TOURIST ATTRACTION IN KAMPUNGBUDAYABETAWISETUBABAKAN SOUTH JAKARTA - Maryetti, Maryetti; Sulistiyowati, Reni (International Conference on Cultural Studies, 2019)
Culture is a reflection of the personality of a nation. Therefore, if the Betawi community no longer has culture, the Betawi community will lose its personality as a core resident of Jakarta who has contributed to improving development in this beloved capital city. A number of Betawi arts can be said to be almost extinct. One of the many Betawi arts whose sound has faded is Lenong's art. In order to keep Lenong Betawi art from becoming extinct it needs to be preserved. The people who live in the Setu Babakan area, directly or indirectly, are the movers and supporters of the Betawi culture that is being raised at the Kampung Budaya Betawi Setu Babakan . Therefore, the community's concern for Lenong Betawi art is important to be explored more deeply, because it is the people who determine whether Lenong Betawi art takes place or not. The main objective of this study is to determine the extent to which Betawi Lenong conservation is carried out. This research is a qualitative descriptive study. Data collection techniques in this study were interviews, observation, study documentation and secondary data. Then the analysis is carried out with the SWOT method. The results of the analysis show that the indigenous people and migrants in the Kampung Budaya Betawi Setu Babakan are optimistic to preserve and develop Betawi culture, especially Lenong Betawi art. They have limited knowledge and understanding of Lenong Betawi art. By directing and fostering the younger generation to continue preserving Lenong Betawi art.